Kajian Pengolahan Limbah Ternak Sapi Potong di Kecamatan Cipatujah Kabupaten Tasikmalaya - Al Faruqi, Ishbar Matin; Badruzzaman, Deden Zamzam; Hidayati, Yuli Astuti (Jurnal Teknologi Hasil Peternakan, 2024)
Processing of waste from beef cattle business is an effort to reduce environmental pollution. Good waste treatment will produce good quality compost. The purpose of this study was to determine the waste treatment process and compost quality including shrinkage (20-60%), odor (no smell), color (dark brown/black), and texture (crumbs). This study uses a survey method. Data collection was carried out by interviews, observations, and organoleptic tests in Cipatujah District on the Harapan 3, Sadar Bakti 3, Sejahtera, Mulyasari livestock groups. The informants were selected using purposive sampling and data were processed through editing and tabulation. The research results show that waste processing in all livestock groups uses the heap and indore methods. The temperature in the composting process includes the mesophilic phase ranges of 27-32°C, thermophilic phase ranges of 37-45°C, decreasing temperature ranges of 26-31°C and cooling and maturation the compost ranges of 20-25°C. Compost quality in Hope Group 3: Shrinkage (50%), Odor (odorless), Color (blackish brown), Texture (crumbs); in the Sadar Bakti Group: Shrinkage (28.7%), Odor (odorless), Color (black), Texture (crumbs); in the Prosperous Group: Shrinkage (50%), Odor (odorless), Color (black), Texture (crumbs); in the Mulyasari Group: Shrinkage (60%), Odor (odorless), Color (black), Texture (slightly sticky).